A nation like all others : a brief history of American foreign relations - Cohen, Warren I. (Columbia University Press, 2018)
In this comprehensive account of American foreign relations from the nation's birth through the Obama administration, Warren I. Cohen confronts the concept of American exceptionalism. A Nation Like All Others offers a brisk, argumentative history that decries the lack of moral imagination in American foreign policy.